2009
DOI: 10.1242/dev.028373
|View full text |Cite
|
Sign up to set email alerts
|

Role of noggin as an upstream signal in the lack of neuronal derivatives found in the avian caudal-most neural crest

Abstract: Neural crest cells (NCCs) arising from trunk neural tube (NT) during primary and secondary neurulation give rise to melanocytes, glia and neurons, except for those in the caudal-most region during secondary neurulation (somites 47 to 53 in the chick embryo), from which no neurons are formed, either in vivo or in vitro. To elucidate this discrepancy, we have specifically analyzed caudal-most NCC ontogeny. In this region, NCCs emerge at E5/HH26, one day after full cavitation of the NT and differentiation of flan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 73 publications
1
21
0
Order By: Relevance
“…After elimination of the cDNA template, single strands were purified and annealed for 5 min at 95°C. dsRNA against Smad1, Foxg1, Noggin and Gremlin (Gont and Lough, 2000;Bardot et al, 2001;Li and Vogt, 1993;Osorio et al, 2009) were used at 0.33 µg/µl, 0.4 µg/µl, 0.25 µg/µl and 0.25 µg/µl, respectively. In the control series, solutions of non-annealed sense and anti-sense RNA strands of the targeted genes were transfected at the same concentration as in the experimental series.…”
Section: Nucleic Acid Preparationmentioning
confidence: 99%
“…After elimination of the cDNA template, single strands were purified and annealed for 5 min at 95°C. dsRNA against Smad1, Foxg1, Noggin and Gremlin (Gont and Lough, 2000;Bardot et al, 2001;Li and Vogt, 1993;Osorio et al, 2009) were used at 0.33 µg/µl, 0.4 µg/µl, 0.25 µg/µl and 0.25 µg/µl, respectively. In the control series, solutions of non-annealed sense and anti-sense RNA strands of the targeted genes were transfected at the same concentration as in the experimental series.…”
Section: Nucleic Acid Preparationmentioning
confidence: 99%
“…233 In the chick trunk, as discussed above, BMP-4/Wnt-1 signals would be required for neuronal progenitor survival prior to migration but dispensable for the melanocyte progeny which instead relies preferentially on Wnt-3a. 230 Likewise, Cre recombinase-fate mapping studies in the mouse trunk showed that GDF-7, a member of the BMP family produced in the dorsal neural tube, restricts a pool of late-emigrating NC cell precursors to the sensory lineage. 234 Finally, very recent data from the Kalcheim's laboratory suggest that in the chick trunk, progenitors of the different NC derivatives are spatially segregated along the ventro-dorsal axis of the neural tube and emigrate in an ordered fashion so that the most ventral sympathetic neurons are generated first while melanocytes migrating dorsally are the last cells to leave the neural tube.…”
Section: Lineage Decisions and Emtmentioning
confidence: 99%
“…226 Lastly, selective cell death has also been found to cause the absence of NC cells in the caudal-most region, but contrary to the hindbrain, it is not due to the presence of BMP-4 combined with Noggin absence. 230 The most caudal region in both mammals and birds is characterized by the absence of motor nerves in the spinal cord and a lack of peripheral ganglia. In the chick embryo, this part of the neural tube corresponds to the region of somites 47-53 which are the last pairs of somites to be formed.…”
Section: Lineage Decisions and Emtmentioning
confidence: 99%
“…Electroporation is a well-established method of gene transfer into neural and mesodermal tissues in chick embryos. Multiple functional studies based on somite and neural tube electroporation have been published (Delfini and Duprez, 2004;Gros et al, 2004Gros et al, , 2009Fournier-Thibault et al, 2009;Osorio et al, 2009). Recently, a gene transfer system by electroporation into aortic endothelial cell has been reported (Rossello and Torres, 2010).…”
Section: Introductionmentioning
confidence: 99%